Molecular basis of nitrogen starvation-induced leaf senescence - Sakuraba, Yasuhito (Frontiers in Plant Science, 2022)
Nitrogen (N), a macronutrient, is often a limiting factor in plant growth, development, and productivity. To adapt to N-deficient environments, plants have developed elaborate N starvation responses. Under N-deficient conditions, older leaves exhibit yellowing, owing to the degradation of proteins and chlorophyll pigments in chloroplasts and subsequent N remobilization from older leaves to younger leaves and developing organs to sustain plant growth and productivity. In recent years, numerous studies have been conducted on N starvation-induced leaf senescence as one of the representative plant responses to N deficiency, revealing that leaf senescence induced by N deficiency is highly complex and intricately regulated at different levels, including transcriptional, post-transcriptional, post-translational and metabolic levels, by multiple genes and proteins. This review summarizes the current knowledge of the molecular mechanisms associated with N starvation-induced leaf senescence.